FICÇÃO CIENTÍFICA CONTRA O CIENTIFICISMO: TEOLOGIA E IMAGINAÇÃO MORAL NA TRILOGIA CÓSMICA DE C. S. LEWIS - CRUZ, PAULO (2016)
This paper presents a study on C. S. Lewis’ Space Trilogy — that embraces Out of the Silent Planet, Perelandra, and That Hideous Strength. We analize the theological concepts used by the author, specially the Original Sin doctrine and its relations with the concept of moral imagination, developed by the american thinker Russell Kirk.